The comfort of lies : a novel - Meyers, Randy Susan (Atria Books, 2013)
"An affair between bright young student Tia and Nathan, a charismatic married sociology professor, ends when Tia becomes pregnant. After urging her to get rid of the baby, Nathan tells his wife, Juliette, about the affair and never sees Tia again. Tia has a daughter and then gives her up for adoption to workaholic pathologist Caroline and her husband, Peter, who dotes on the child. Five years later, Juliette intercepts a letter from Tia that starts, "Dear Nathan, This is our daughter." Inside is a photo of the girl, Savannah, and a promise to "help her get in touch" with Nathan in the future. Her trust in Nathan strained once more, Juliette goes in search of Caroline, who regrets neglecting Savannah."--Publishers Weekly.